Comparison between caudal epidural and ultrasound-guided ilioinguinal-iliohypogastric block with bupivacaine and dexmedetomidine for postoperative analgesia following pediatric inguinal hernia surgeries: A prospective randomized, double-blind study - R Varsha; Sameer N Desai; Mahantesh S Mudakanagoudar; Venkatesh M Annigeri (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Caudal epidural and ultrasound-guided ilioinguinal, iliohypogastric nerve (IL/IH) blocks are commonly used regional anesthesia techniques for postoperative analgesia in pediatric inguinal surgeries. Dexmedetomidine as an adjuvant has been proven to prolong the duration of both neuraxial and peripheral nerve blocks. We compared the duration of analgesia provided by local anesthetic (LA) and dexmedetomidine for caudal and IL/IH block for pediatric inguinal surgeries. Material and Methods: Forty-six children undergoing inguinal hernia repair were selected for this randomized double-blind study. After general anesthesia, children received either 0.75 mL.kg−1 of 0.25% bupivacaine with 1 mcg.kg−1 of dexmedetomidine in caudal epidural or 0.25 mL.kg−1 of 0.25% bupivacaine with 1 mcg.kg−1 of dexmedetomidine in IL/IH block. The pain was assessed up to 24 h postoperatively using face, legs, activity, cry, consolability (FLACC) score. For FLACC ≥4, rescue analgesia was provided using 1 μg/kg of intravenous fentanyl, up to 2 h postoperatively and 10 mg/kg of oral ibuprofen between 2 and 24 postoperative hours. The time for first rescue analgesia was taken as the duration of analgesia. Results: There were no significant differences in the pain scores or analgesic utilization between the groups. The duration of analgesia of caudal and IL/IH blocks was similar (720.3 ± 430.1 min and 808.4 ± 453.1 min, respectively). The time taken for the performance of block was significantly higher for caudal compared to IL/IH (547 ± 93 vs. 317 ± 179 s; P < 0.001). Conclusion: Both caudal epidural and USG-IL/IH block with dexmedetomidine as additive provide the comparable duration of postoperative analgesia with no significant side effects.